Selective Utilization of N-acetyl Groups in Chitin for Transamidation of Amines - Xin, Yu; Shen, Xiaojun; Liu, Huizhen; Han, Buxing (Frontiers in Chemical Engineering, 2021)
The selective transformation of chitin into various renewable N-containing chemicals and medicines has attracted increasing attention. However, the N-acetyl groups in chitin construct strong hydrogen bond networks, which restricts its depolymerization and transformation. The selective conversion of robust chitin commonly requires considerable base catalysts to remove the N-acetyl group as a byproduct in advance, which is non-compliance with the principle of atomic economy. Herein, for the first time we demonstrate a novel approach to achieve the selective utilization of the N-acetyl group in chitin for transamidation of chitin with amines. A series of amine derivatives, mainly including aliphatic amine, cyclic amine and functionalized aromatic amine, could be selectively converted into the corresponding amide products frequently found in pharmaceuticals. Furthermore, the solid residue after removing the acetyl group (denoted as De-chitin) with the sufficient exposure of -NH2 groups as a solid base catalyst shows excellent performance in the aldol condensation reaction of furfural and acetone to produce fuel precursors. Our process provides a strategy that exploiting every functional group adequately in substrates to obtain value-added chemicals.